Ответы и объяснения

2013-05-02T20:03:44+00:00

x(x+1)(x-10)=(x-1)(x-3)(x-5)
(x^2+x)*(x-10)-(x-1)*(x-3)*(x-5)=0

x^3-9x^2-10x-(x-1)*(x-3)*(x-5)=0

x^3-9x^2-10x-(x^2-4x+3)*(x-5)=0

x^3-9x^2-10x-(x^3-9x^2+23x-15)=0

x^3-9x^2-10x-x^3+9x^2-23x+15=0

-9x^2-10x+9x^2-23x+15=0

-10x-23x+15=0

-33x+15=0

x=-(-15)/33

x=15/33

x=5/11

(x-1)(x-4)(x+7)=x(x+1)^2

(x^2-5x+4)*(x+7)-x*(x+1)^2=0

x^3+2x^2-31x+28-x*(x+1)^2=0

x^3+2x^2-31x+28-x*(x^2+2x+1)=0

x^3+2x^2-31x+28-(x^3+x^2*2+x)=0

x^3+2x^2-31x+28-x^3-x^2*2-x=0

2x^2-31x+28-x^2*2-x=0

-31x+28-x=0

-32x+28=0

x=-(-28)/32

x=28/32

x=0.875